Interfibrillar packing of bovine cornea by table‐top and synchrotron scanning SAXS microscopy. Issue 4 (14th July 2016) - Sibillano, T.; De Caro, L.; Scattarella, F.; Scarcelli, G.; Siliqi, D.; Altamura, D.; Liebi, M.; Ladisa, M.; Bunk, O.; Giannini, C.
Abstract : Bovine cornea was studied with scanning small‐angle X‐ray scattering microscopy, by using both synchrotron radiation and a microfocus laboratory source. The supramolecular structure of the collagen fibers is explored thanks to the combination of statistical (adaptive binning and canonical correlation analysis) and crystallographic (pair distribution function analysis) approaches. Abstract : Bovine cornea was studied with scanning small‐angle X‐ray scattering (SAXS) microscopy, by using both synchrotron radiation and a microfocus laboratory source. A combination of statistical (adaptive binning and canonical correlation analysis) and crystallographic (pair distribution function analysis) approaches allowed inspection of the collagen lateral packing of the supramolecular structure. Results reveal (i) a decrease of the interfibrillar distance and of the shell thickness around the fibrils from the periphery to the center of the cornea, (ii) a uniform fibril diameter across the explored area, and (iii) a distorted quasi‐hexagonal arrangement of the collagen fibrils. The results are in agreement with existing literature. The overlap between laboratory and synchrotron‐radiation data opens new perspectives for further studies on collagen‐based/engineered tissues by the SAXS microscopy technique at laboratory‐scale facilities.